Genetic Diversity in Introduced Golden Mussel Populations Corresponds to Vector Activity - Ghabooli, Sara (2013)
We explored possible links between vector activity and genetic diversity in introduced populations of Limnoperna fortunei by characterizing the genetic structure in native and introduced ranges in Asia and South America. We surveyed 24 populations: ten in Asia and 14 in South America using the mitochondrial cytochrome c oxidase subunit I (COI) gene, as well as eight polymorphic microsatellite markers. We performed population genetics and phylogenetic analyses to investigate population genetic structure across native and introduced regions. Introduced populations in Asia exhibit higher genetic diversity (HE = 0.667–0.746) than those in South America (HE = 0.519–0.575), suggesting higher introduction effort for the former populations. We observed pronounced geographical structuring in introduced regions, as indicated by both mitochondrial and nuclear markers based on multiple genetic analyses including pairwise FST, FST, Bayesian clustering method, and three-dimensional factorial correspondence analyses. Pairwise FST values within both Asia (FST = 0.017–0.126, P = 0.000–0.009) and South America (FST = 0.004–0.107, P = 0.000–0.721) were lower than those between continents (FST = 0.180–0.319, P = 0.000). Fine-scale genetic structuring was also apparent among introduced populations in both Asia and South America, suggesting either multiple introductions of distinct propagules or strong post-introduction selection and demographic stochasticity. Higher genetic diversity in Asia as compared to South America is likely due to more frequent propagule transfers associated with higher shipping activities between source and donor regions within Asia. This study suggests that the intensity of human-mediated introduction vectors influences patterns of genetic diversity in nonindigenous species